Understanding handling performance of rugby balls under wet conditions: analysis of finger-ball friction - Liu, J.; Zhang, Q.; Liu, X. (International Journal of Performance Analysis in Sport, 2020)
This paper presents work with the aim of investigating the effect of moisture on the skin frictional behaviour of human finger-pads in contact with rugby balls. During sports activities, human body experiences high volumes of thermoregulatory sweating as a result of achieving body`s temperature balance. Consequently, sweating alters human skin properties and contact conditions between hand skin and sports equipment, and may adversely affect exercise/sports performance. In this work, a rugby ball passing test under wet conditions was conducted to examine the influence of skin hydration on rugby ball handling performance. Then, a comprehensive study was carried out to assess skin structures, frictional properties and contact areas of the interface between human finger-pads and flat surfaces at different moist conditions. It was found that the handling performance of rugby balls is strongly associated with the skin moisture level. The experimental results of the skin friction study showed that the skin friction coefficient changes with hydration time following a "bell-shape" curve. It also showed that the corresponding thickness of the stratum corneum of the examined fingers increased due to the transmission of water in skin tissues. This leads to an increase in the contact area and friction force with hydration time.